Calcium Carbonate Content and Proximate Composition of Chicken Eggshell Flour at Different Oven Temperatures - Ningrum, E. M.; Suharto, R.H.; Al Kautsar, A.M.F.; Hakim, M.A. (Hasanuddin Journal of Animal Science (HAJAS), 2025)
Eggshells, a common household waste product, are rich in calcium carbonate, which constitutes approximately 90% of their composition. The weight of an eggshell typically accounts for 9-12% of the total egg weight. In Indonesia, calcium intake is still relatively low compared to the Recommended Dietary Allowance (RDA) of 1000-1200 mg/day, leading to deficiencies that affect bone health and increase the risk of diseases such as osteoporosis. This study aims to explore the potential of chicken eggshell waste as a valuable source of calcium carbonate, an abundant yet underutilized material. While eggshell waste can contribute to environmental pollution due to microbial activity, its recycling offers a sustainable solution. By converting eggshells into flour, food products can be enriched with calcium. For instance, eggshell flour at a 0.4% concentration has been successfully incorporated into various food products such as baked puddings, ice cream, cakes, muffins, yeast rolls, popovers, and mayonnaise. Studies have shown that this addition significantly increases calcium content without affecting the taste or cooking quality of the food. The primary objective of this research is to produce calcium carbonate from chicken eggshell waste, thus providing a sustainable approach to waste recycling and creating a valuable, nutritious product. The findings of this study could have significant benefits for the community by reducing waste, particularly from chicken eggshells, while transforming them into a beneficial resource for human health. Keywords: Waste, eggshell, calcium carbonate